Advanced Thyroid and Parathyroid Ultrasound - Milas, Mira; Mandel, Susan J.; Langer, Jill E. (Springer International Publishing : Imprint: Springer, 2017)
This textbook provides a comprehensive, state-of-the art review of ultrasound in thyroid and parathyroid diseases, and will serve as a valuable resource for all clinicians and allied healthcare providers who wish to advance their knowledge and skills in sonography. Although a novice sonographer will be able to understand all of the topics, these are presented from a vantage point of complex decision-making encountered in real clinical scenarios. The sections are organized according to a logical structure covering benign and malignant thyroid conditions, parathyroid disease, and ultrasound technology, ultrasound-guided interventions, and innovations. The style of the chapters provide practical, actionable information that is richly illustrated with figures and links to video cine-clips, as these form the real-time advantage of ultrasound compared to other imaging modalities. Since thyroid and parathyroid ultrasound is now mainly clinician-performed, the chapter topics aim to show how different specialists uniquely apply ultrasound in given clinical scenarios. The text illustrates the optimal incorporation of current practice guidelines, as this remains varied and inconsistent among clinicians. The content is written by invited experts who perform ultrasound in their daily clinical practices and participate in teaching ultrasound nationally and internationally. It conveys the most up-to-date scientific and clinical information in an interactive and visual format. Advanced Thyroid and Parathyroid Ultrasound fills a gap in currently available resources by serving as a single resource unifying information relevant to multiple specialists interested in advanced thyroid and parathyroid ultrasound. It provides a practical, concise yet comprehensive summary of the current status of the field that will help guide patient management.
Keywords: Medicine.; Radiology.; Endocrinology.; Otolaryngologic surgery.; Surgery.; elektronické knihy; electronic books